Assessment and correction of local antimicrobial protection factors in women with chronic recurrent vulvovaginal candidiasis and type 2 diabetes mellitus - Oksana A. Gizinger; Elena N. Andreeva (IP Berlin A.V., 2024)
Aim. Evaluation and correction of local antimicrobial protection factors in women with type 2 diabetes mellitus (DM 2) and chronic recurrent vulvovaginal candidiasis (rVVC). Materials and methods. The study involved 100 women undergoing outpatient follow-up at the age of 40.9±5.8 years, with a body mass index of 29.8±3.5. The period was 2022-2023. The examination included anamnesis, collection of anthropometric data, calculation of body weight, microscopic examination of smears from the cervical canal and vagina, Gram-stained before treatment, in the 1st and 3rd months after its completion, identification pathogenic microorganisms using PCR, colposcopy, ultrasound of the pelvic organs. Indicators of glycosylated hemoglobin in the subjects at the control points of the study: at 1 month the average values were 5.9±2.9%, at 3 months - 5.9±3.0%, the average value was 5.9±3.1%. Candida species were identified by the bacteriological method using Sabouraud dextrose agar (growth of colonies of fungi of the genus Candida in an amount of more than 103 CFU/ml). Immunological methods for studying antimicrobial protection factors included studying the number of neutrophil granulocytes (NG) on the surface of the mucous membranes of the vulva and vagina, their phagocytic and NBT-reducing activity in a latex test. Randomization of patients into groups: group 1 included 50 (50%) women with DM 2 who, as part of complex therapy for rVVC received the drug Genferon® 1 intravaginal suppository of 500 thousand units 2 times a day for 10 days and fluconazole 150 mg orally three times with an interval of 72 hours at the first stage of treatment; group 2 included 50 (50%) women who received therapy with fluconazole 150 mg three times with an interval of 72 hours. The maintenance anti-relapse course therapy in both groups included the use of fluconazole 150 mg once a week for 6 months. In group 1st anti-relapse therapy was supplemented by the administration of the drug Genferon® 1 intravaginal suppository of 500 thousand units at night 3 times a week for 3 months, after which the vaginal microbiota was corrected for 2 weeks using vaginal suppositories, containing Lactobacillus acidophilus in an amount of at least 108 CFU. In group 2nd, basic anti-relapse antimycotic therapy was not accompanied by the prescription of any immunomodulatory or probiotic drugs. Results. The etiological agents of rVVC in women of late reproductive age in 79% (n=79) и 28% (n=28), respectively, were C. albicans and C. glabrata, which during the period of acute of the disease were detected by culture in the vaginal discharge at more than 104 CFU/ml. Chronic recurrent course of vulvovaginal candidiasis in women with DM 2 was characterized by exacerbations 4 or more times a year, accompanied by the corresponding clinical picture: white or yellowish-white cheesy discharge from the genital tract, itching or burning in the anogenital area, discomfort in the external genital area, dyspareunia, dysuria, decreased phagocytic activity of NG in vaginal secretions by 25.8%, impairment of their spontaneous and latex-induced NBT-reducing activity by 35.2%, functional reserve by 23.0% relative to reference values. The use of the drug Genferon® as part of complex therapy for rVVC contributed to a decrease in the number of Candida spp. in 1st and 3d months of observation after completion of anti-relapse therapy, normalization of cellular factors of innate immunity of the mucous membranes, faster resolution of the clinical manifestations of an episode of the disease. The decrease in the number of relapses over a 12-month observation period compared to the control group was also facilitated by an increase in the protective properties of the vaginal mucosa due to the restoration of the vaginal microbiota with the help of lactobacilli acidophilus. Conclusion. The etiological agents of rVVC in women of late reproductive age are C. albicans and C. glabrata. Subcompensated DM 2 is a risk factor for rVVC, which requires additional monitoring of microbiological parameters of the vaginal microbiota. rVVC in women with DM 2 is associated with an increase in the number of NG in the vaginal secretion, a decrease in their phagocytic activity and functional reserve compared to the reference values. Combination therapy of rVVC with topical recombinant interferon α2b, benzocaine and taurine in the formulation of Genferon® (suppositories) is an effective method to improve the clinical and immunological efficacy of therapy.